Interferon‐alpha‐induced hepatitis C virus clearance restores p53 tumor suppressor more than direct‐acting antivirals. Issue 3 (28th March 2017) - Aydin, Yucel; Chatterjee, Animesh; Chandra, Partha K; Chava, Srinivas; Chen, Weina; Tandon, Anamika; Dash, Asha; Chedid, Milad; Moehlen, Martin W; Regenstein, Frederic; Balart, Luis A; Cohen, Ari; et al.
Abstract : The mechanism why hepatitis C virus (HCV) clearance by direct‐acting antivirals (DAAs) does not eliminate the risk of hepatocellular carcinoma (HCC) among patients with advanced cirrhosis is unclear. Many viral and bacterial infections degrade p53 in favor of cell survival to adapt an endoplasmic reticulum (ER)‐stress response. In this study, we examined whether HCV clearance by interferon‐alpha or DAAs normalizes the ER stress and restores the expression of p53 tumor suppressor in cell culture. We found that HCV infection induces chronic ER stress and unfolded protein response in untransformed primary human hepatocytes. The unfolded protein response induces chaperone‐mediated autophagy (CMA) in infected primary human hepatocytes and Huh‐7.5 cells that results in degradation of p53 and induced expression of mouse double minute 2 (Mdm2). Inhibition of p53/Mdm2 interactions by small molecule (nutlin‐3) or silencing Mdm2 did not rescue the p53 degradation, indicating that HCV infection induces degradation of p53 independent of the Mdm2 pathway. Interestingly, we found that HCV infection degrades p53 in a lysosome‐dependent mechanism because lysosome‐associated membrane protein 2A silencing restored p53 degradation. Our results show that HCV clearance induced by interferon‐alpha‐based antiviral therapies normalizes the ER‐stress response and restores p53, whereas HCV clearance by DAAs does neither. We show that decreased expression of p53 in HCV‐infected cirrhotic liver is associated with expression of chaperones associated with ER stress and the CMA response. Conclusion : HCV‐induced ER stress and CMA promote p53 degradation in advanced liver cirrhosis. HCV clearance by DAAs does not restore p53, which provides a potential explanation for why a viral cure by DAAs does not eliminate the HCC risk among patients with advanced liver disease. We propose that resolving the ER‐stress response is an alternative approach to reducing HCC risk among patients with cirrhosis after viral cure. ( Hepatology Communications 2017;1:256‐269)